2002
DOI: 10.1007/s00259-001-0711-3
|View full text |Cite
|
Sign up to set email alerts
|

Initial results in the assessment of multiple myeloma using 18F-FDG PET

Abstract: This prospective study was undertaken to investigate the appearance of multiple myeloma on fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET). Furthermore, the accuracy of FDG-PET in detecting myeloma lesions and its influence on patient management were evaluated. Forty-three patients with known multiple myeloma (n=28) or solitary plasmacytoma (n=15) underwent FDG-PET. The results of routinely performed radiographs and of scans obtained using all available imaging modalities (MRI, CT), as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(83 citation statements)
references
References 11 publications
2
76
0
4
Order By: Relevance
“…The studies with a methodological quality above average were the studies by Bredella et al, 10 Fonti et al, 14 Hur et al, 16,17 Schirrmeister et al, 23,24 and Zamagni et al 4,21 Comparison of 18 FDG PET or PET-CT and Conventional Imaging at Staging Of the 18 studies conducted, concordance assessment between WBXR and 18 FDG PET scan was possible in 7 (concerning 242 patients). In 6 out of these 7 studies, 18 FDG PET (with or without CT) scan showed more lytic lesions then conventional WBXR with the exception of lytic lesions located in the skull 4,[9][10][11]19,21,23,24 (Table 5). Two studies compared 18 FDG PET-CT scan with WBXR.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies with a methodological quality above average were the studies by Bredella et al, 10 Fonti et al, 14 Hur et al, 16,17 Schirrmeister et al, 23,24 and Zamagni et al 4,21 Comparison of 18 FDG PET or PET-CT and Conventional Imaging at Staging Of the 18 studies conducted, concordance assessment between WBXR and 18 FDG PET scan was possible in 7 (concerning 242 patients). In 6 out of these 7 studies, 18 FDG PET (with or without CT) scan showed more lytic lesions then conventional WBXR with the exception of lytic lesions located in the skull 4,[9][10][11]19,21,23,24 (Table 5). Two studies compared 18 FDG PET-CT scan with WBXR.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Finally, 18 studies involving 798 patients were included in this systematic review (Figure 1). 3,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] There was no disagreement between the reviewers regarding the inclusion of the articles. The characteristics of the included studies are presented in Table 2.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Active myeloma is positive on PET scan. 31,32 PET/ CT and MRI scans are more sensitive than plain radiographs and are indicated when symptomatic areas show no abnormality on routine radiographs. FDG PET/CT results after induction therapy and stem cell transplant (SCT) help in predicting the prognosis of patients with symptomatic MM.…”
Section: Additional Diagnostic Testsmentioning
confidence: 99%
“…Several studies have demonstrated that they are informative in SPB and upstage a proportion of patients. 16,[18][19][20] In a retrospective analysis, Warsame and colleagues suggested that the outcome in patients has improved since the introduction of routine PET imaging at their center because the outcome in patients with a negative PET scan was superior to those in whom PET was not performed. 10 Similarly, Fouguet et al have recently demonstrated that additional lesions on PET imaging are associated with progression to MM.…”
Section: ) (B)mentioning
confidence: 99%